Changing Preferences for a Cervical Cancer Screening Strategy: Moving Away from Annual Testing - Elizabeth Schrier; Hunter K. Holt; Miriam Kuppermann; George F. Sawaya (Mary Ann Liebert, 2022)
Background: While annual cytology has not been recommended for many years, it remains many patients' preferred screening strategy for cervical cancer. Patient education and provider recommendations have been found effective in aligning professional society guidelines with patient preferences. We assessed whether an educational video with value elicitation exercises (utility assessments) changed screening strategy preferences among patients who had an initial preference for annual screening. Materials and Methods: We conducted an interventional study of English- or Spanish-speaking women 21?65 years of age, recruited from two women's health clinics in San Francisco, California (n?=?262). Participants were asked about their preferred method of screening before viewing a 7-minute educational video and using a computerized tool that elicited values for 23 different health states related to cervical cancer screening. Directly afterward, they were again asked about their preferred screening strategy. Multivariable regression analysis was utilized to identify independent predictors of changing preferences. Results: Of 246 enrollees, 62.6% (154/246) had an initial preference for annual cytology; after viewing the video and completing the values elicitation exercises, about half (72/154, 47%) preferred a strategy other than annual screening. Having attended college and being screened every 3 to 5 years in the recent past were independent predictors of changing preferences away from annual screening. In sensitivity analyses, 53.2% of average-risk participants changed preferences away from annual cytology (p?<?0.01). Conclusions: Viewing an educational video and conducting a series of value elicitation exercises were associated with a substantially decreased likelihood of preferring annual screening. These findings underscore the importance of patient-centered education to help support informed patient preferences.